Dual‐templating surface gel into thin SSZ‐13 zeolite membrane for fast selective hydrogen separation: Special Issue: Emerging Investigators. Issue 6 (30th September 2022) - Rong, Huazhen; Guan, Yixing; Li, Jun; Li, Ziyi; Ma, Dan; Zhang, Jingjing; Liu, Terence Xiaoteng; Zou, Xiaoqin
Abstract: Highly permeable zeolite membranes are desirable for fast gas separation in the industry. Reducing the membrane's thickness is deemed to be an optimal solution for permeability improvement. Herein, we report the synthesis route of thin SSZ‐13 zeolite membranes via the conversion of template‐contained surface gels. The synthesis gel is fully crystallized into crack‐free SSZ‐13 membranes assisted with dual templates of N, N, N ‐trimethyl‐1‐adamantammonium hydroxide (TMAdaOH) and tetraethylammonium hydroxide (TEAOH). The specific functions of TMAdaOH for structure directing and TEAOH for crystallization regulating are well discussed. Thin surface gel layer is impregnated onto porous alumina with subsequent crystallization into a 500 nm thick membrane. This submicron‐thick membrane exhibits high H2 permeance with 50 × 10 −8  mol s −1  m −2  Pa −1 during hydrogen separation. Meanwhile, the separation factors are retained around 23.0 and 31.5 for H2 /C2 H6 and H2 /C3 H8, respectively. This approach offers a possibility for obtaining high‐quality zeolite membranes for efficient hydrogen separation. Abstract : Submicron SSZ‐13 zeolite membranes in high continuity were synthesized from dual‐templated surface gels. The templates directed and regulated the crystallization of the SSZ‐13 zeolite, and the surface gel determined the thickness of the membrane. The synthesized membranes possessed good hydrogen separation performances in terms of permeance and separation factor for H2/C2H6 and H2/C3H8 mixtures.